‘Placing’ Caring Relationships in Education: Addressing Abstraction and Domination - Rushmere, Andrew Tyler (Paideusis, 2007)
The purpose of this paper is twofold: to underscore the possible dangers of abstraction, objectification and reification as roots of human domination over other human and non-human beings; and to suggest that, as one possibility, place-based education, can counter these dominating patterns by pulling up their roots through fostering relational ontologies based on care and emotional/sensuous experience. The author will foreground the work of Henri Lefebvre, Neil Evernden, and R. D. Laing in the abstraction discussion, while the discussion of place-based education will draw largely on the writings of David Gruenewald.